Navigating the HyFlex Horizon: Uncovering Successes and Hurdles in HyFlex Undergraduate Education - Morrison, Laura; Kay, Robin; Mann, Alison; Tepylo, Diane; Atkinson, Hannah; Brodie, Iain (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2025)
Since the COVID-19 pandemic, the demand for flexible, online learning models has increased in postsecondary education. The HyFlex approach, where students can attend class online or in-person, has emerged as one popular option. However, there remains limited research on implementing HyFlex in non-lecture undergraduate learning environments. This study investigated the affordances and challenges of HyFlex in non-lecture settings through the lens of the Community of Inquiry framework. Using a participatory action research design, data were collected from instructor-researcher field notes, video debriefs, and student interviews. A thematic analysis revealed that flexibility is the main affordance of the HyFlex model. Significant challenges emerged with attaining mode neutrality and managing technological issues related to audio and video quality. Practical implications include providing institutional support in the form of enhanced technical infrastructure and training for instructors. Limitations to the study include a small sample size, demographic homogeneity, self-report data, and a limited focus on learning outcomes. Future research approaches are offered to address challenges in HyFlex design.